What They Actually Feel: A Different Perspective of Assessment through E-Learning - Hadianti, Siti (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
Teaching through e-learning platforms is a common activity deliberately performed by Open University. Later, this process escalated and transformed into a trend due to the advanced development of technology and unforeseen phenomena like the COVID-19 pandemic. However, teaching and learning within the platform are not equally similar in terms of sense and practice. Particularly, assessing student progress and reflecting on the learning process that has been done might not be as easy as what conventional or offline classes can offer. This research provides one particular way to assess it. Through the eyes of students as well as tutors, we could also gain valuable information regarding how learning within e-learning environments has been performed. This research applied qualitative analysis with the help of questionnaire, as well as NVivo as the tool for natural language processing analysis. A total of 66 tutors and approximately 471 students were involved. Based on the findings and analysis, it is shown that tutors tend to mention 7 frequent words, while students mention 8 words. Each word was analyzed by the researcher, leading to two conclusions for tutors. They perceived that the teaching process was hindered by students’ constraints and technical issues. Meanwhile, students faced problems related to slow feedback, lack of communication, and clarity, especially toward students’ answers.